Supramolecular fluorogenic peptide sensor array based on graphene oxide for the differential sensing of ebola virus - Fu, Meng-Qi; Wang, Xu-Chen; Dou, Wei-Tao; Chen, Guo-Rong; James, Tony D; Zhou, Dong-Ming; He, Xiao-Peng (Chemical communications (Cambridge, England), 2020)
We report on a supramolecular sensor array using fluorogenic peptide probes and graphene oxide that can target glycoproteins on a viral caspid, facilitating the differentiation of ebola virus from marburg virus and receptor-extensive vesicular stomatitis virus using principal component analysis. Principal component analysis of a fluorescent supramolecular sensor array based on graphene oxide can be used to differentiate ebola virus from marburg virus and receptor-extensive vesicular stomatitis virus.